Omega-3 polyunsaturated fatty acid supplementation, sports performance and recovery - James, L. (2021)
Strategies focused on the enhancement of recovery from exercise and the subsequent improvement in sport performance are continually being sought by athletes. One strategy that has received considerable attention within the sports nutrition literature is omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation. The myriad of proposed health benefits has led to the investigation of dietary supplementation to enhance recovery from exercise due to the anti-inflammatory properties and whether this ultimately results in improved sports performance. The overall aim of this thesis was to establish whether n-3 PUFA supplementation could improve exercise performance and recovery from strenuous exercise. To achieve this aim a series of studies were conducted on trained and untrained males, in both lab and field-based studies. There was no significant effect of n-3 PUFA supplementation on cycling time trial performance or associated physiological parameters (chapter 4). This finding was also observed in strength and power indices in untrained individuals following 3 weeks supplementation (chapter 5) and trained rugby union players following 6 weeks supplementation (chapter 6). However, muscle damage, measured by the reduction in peak isometric torque following exercise-induced muscle damage (EIMD), was lower following 3 weeks of n-3 PUFA supplementation (chapter 5), suggesting supplementation may aid the recovery process in untrained individuals. No changes were observed in biomarkers of muscle damage post-exercise following supplementation (chapter 4, 5 and 6). When supplementation was combined with resistance training there was no additive effect of supplementation in terms of strength and power performance or recovery from EIMD. The increase in strength and power observed as a result of the resistance training was not negatively impacted with the addition of supplementation in untrained males (chapter 5). When supplementation was implemented within an applied sports setting, elite rugby union players, the increases in power observed mid-season were not different between supplemented and non-supplemented groups (chapter 6). No changes were observed in the recovery from resistance-based training or game play with the addition of supplementation (chapter 6). In conclusion, this thesis has observed an attenuation of the strength deficit caused by EIMD with n-3 PUFA supplementation in untrained males, but no positive impact of supplementation on performance or recovery within the context of cycling or rugby union. There was no additive effect of supplementation when combined with resistance training on improvements in strength and power. However, there was no negative impact of supplementation on any performance indicators suggesting that n-3 PUFAs do not blunt training adaptations.